1970
DOI: 10.1258/002367770781071554
|View full text |Cite
|
Sign up to set email alerts
|

A simplified fibreglass germ-free isolator with facilities for performing dental surgery on rats

Abstract: An isolator constructed in fibreglass was equipped with facilities for performing dental surgery on germ-free rats and then maintaining them in the germ-free state for a period following the surgical procedure. The main unit was sterilised with peracetic acid, and the ancillary equipment by gamma radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1971
1971
1987
1987

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The system was adopted in the germ-free animal laboratory at Allington Farm, Porton, in September 1969 and is currently in use there. It was subsequently used in the germ-free animal laboratory at the Department of Oral Medicine, Guys Hospital (Paterson, Jones, Cook & Garriock, 1970). Workers in both laboratories found that the time spent on the packaging of materials was much reduced, and it was convenient to be able to dispense with the heat-sealing of plastic films.…”
Section: Discussionmentioning
confidence: 99%
“…The system was adopted in the germ-free animal laboratory at Allington Farm, Porton, in September 1969 and is currently in use there. It was subsequently used in the germ-free animal laboratory at the Department of Oral Medicine, Guys Hospital (Paterson, Jones, Cook & Garriock, 1970). Workers in both laboratories found that the time spent on the packaging of materials was much reduced, and it was convenient to be able to dispense with the heat-sealing of plastic films.…”
Section: Discussionmentioning
confidence: 99%